Effects of fluid intake and loss on performance in athletes: A systematic review - Gençay, E.; Gençay, S. (International Journal of Physical Education, Sports and Health, 2024)
Drinking enough fluids is an important part of a sports diet. Because adequate hydration helps performance and protects the organism against medical hazards. Most of the information about fluid intake often causes confusion about what to drink, when and how much. 15-20 years ago, it was said that fluids should not be consumed before or during exercise. However, today, it is stated through excessive commercial advertisements that sports drinks should be used as much as possible (7). As it is known, approximately 60% of the human body is water, and it is stated that when this water balance is disrupted by water loss, performance is affected and even death may occur if the water loss is too much (14). The aim of this study, which was carried out with the literature review method; It aims to reveal the fluid intake of athletes and the effects of loss on performance, the changes in the organism due to fluid loss, the amount, content, timing and similar features of the fluid to be taken.